How the presence of others shapes the user experience of service robots - Tretter, Stefan; von Terzi, Pia; Diefenbach, Sarah (Frontiers in Robotics and AI, 2025)
In the age of mobile and self-service technologies, human-computer interaction (HCI) often takes place in public settings. Such interactions can be considered a performance in front of others, when the relationship with potential observers may affect user preferences for different interaction styles. From a psychological perspective, public interactions may feel embarrassing or disturbing, but they also provide the opportunity for favorable self-presentation or connection with others. The present study investigated how the presence of different observers (i.e., acquaintance, stranger) emphasizes different psychological needs and, in turn, affects preferences for more or less expressive interactions with a service robot. Results show that users’ need for relatedness was higher when imagining a robot interaction with close observers, while popularity was more important with unknown observers. Relatedness was directly linked to a preference for more expressive interactions, regardless of the expected outcome. In contrast, popularity led to stronger expressivity preferences only when users anticipated a successful interaction for which they could take credit. Our research provides valuable insights into the impact of user-observer-relationship on public HCI, and can inspire designers to take into account how present others and users’ expectation of successful outcomes may call for different degrees of expressivity in interaction design.